Antioxidant Effect of Shuidouchi - Jing Zhang; Qin Li; Yang Wei; Xingyao Long; Jianfei Mu; Yanni Pan; Xin Zhao (Functional Effects of Fermented Soybean Food in China, 2021)
Shuidouchi is a traditionally fermented soybean product in China. Shuidouchi production requires a variety of processes; however, the production process has not been standardized. It can be developed into high-quality products with enhanced health effects by improving the design of its fermentation process and increasing the content of its active ingredients. In this study, a single-factor experiment was conducted that established different process conditions to determine the fermentation conditions that achieve the highest content of active ingredients and the best in vitro antioxidant effect. The effect of Shuidouchi on the prevention of dextran sulfate sodium-induced colitis in mice was also observed. The obtained results indicated that the optimal process conditions involved soaking for 12 h, placement in a glass container, and fermentation at 35°C for 48 h. Shuidouchi that was fermented under such conditions had the highest level of soybean isoflavones and exerted greater antioxidant effects than if fermented under other conditions. The Shuidouchi extract (soaking twice the quantity of water for 12 h, placing in a glass container, and fermenting at 35°C for 48 h) obtained by using the optimal fermentation process can prevent the shortening of the colon and increase the weight-to-length ratio of the colon that is caused by colitis. Shuidouchi extraction not only effectively reduces the disease activity index and the levels of serum endothelin (ET), substance P (SP), and interleukin-10 (IL-10), it also increases the levels of somatostatin (SS), vasoactive intestinal peptide (VIP), and interleukin-2 (IL-2) of mice with colitis. In addition, Shuidouchi extraction increased the levels of glutathione (GSH) and superoxide dismutase (SOD) in colitis mice; in contrast, Shuidouchi decreased the levels of myeloperoxidase (MPO) and malondialdehyde (MDA) in the colon of mice with colitis. Further detection of mRNA in colon tissues showed that Shuidouchi extraction can upregulate the expression of neuronal nitric oxide synthase (nNOS), endothelial nitric oxide synthase (eNOS), c-Kit, and the stem cell factor (SCF). Furthermore, it can downregulate the expression of inducible nitric oxide synthase (iNOS), interleukin-8 (IL-8), and C-X-C chemokine receptor type 2 (CXCR2) in the colon of mice with colitis. Further experimental results showed that Shuidouchi could reduce the protein expression of interleukin 6 (IL-6), IL-12, and tumor necrosis factor-\(α\) (TNF-\(α\)) in colitic mice. Therefore, the improved processing of Shuidouchi inhibits colitis, which is directly related to the high content of soybean isoflavones.